The Effectiveness of an Educational Program in Developing the Skill of Reading the Map among Kindergarten Children - Mouhesin , Zaman Kareem (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to identify the effectiveness in developing the skill of reading the map among kindergarten children.To achieve the research objectives, the researcher derived the following hypotheses : There is no statistically significant difference between the mean scores of the experimental group children on the map reading skill test for kindergarten children for both pre and post applications.There is no statistically significant difference between the mean scores of children between the mean scores of the experimental group and the scores of the children of the control group on the map reading skill test for kindergarten children for the post application.There is no statistically significant difference between the mean scores of the experimental group children on the map reading skill test for kindergarten children for the following and tracking applications.The research sample consisted of one kindergarten, and the number of children of the introductory (220) boys and girls, by (120) males and (100) females. Using the statistical bag (SPSS), the research reached the following results: There are statistically significant differences between the mean scores of the pre and posttests of the experimental group on the skill of reading the map and this difference in favor of the post test. The statistically significant differences between the mean scores of the experimental group and the average scores of the control group on the test reading skill in the post test